Demographic Profile and Outcome of Covid- 19 Obstetric Patients Undergoing Caesarean Section in a Tertiary Care Government Hospital in Dhaka, Bangladesh - Akter, Shamima; Miah, Mohammad Abdul Karim; Mohammad, Taneem; Rahman, Md Siddiqur; Bhuiyan, Md Abdullah Tareq; Zunaid, Md (Journal of Dhaka Medical College, 2024)
Background: Pregnancy itself is a hypercoagulable state. COVID-19 infection makes it more deleterious. As a consequence of exaggerated inflammatory response in COVID 19 infected mothers, there is alterations of coagulation system occurs, causing thrombi (micro and macro) in various organs reducing blood flow in capillaries , followed by emboli formation mainly in lung, heart, brain and kidney, resulting in multiple organ failure even death. The present study aims to observe retrospectively the clinical outcome of parturients with COVID-19 infection undergoing caesarean sections. Methods: This observational study was done in the COVID dedicated operation theatre of Department of Anaesthesia, Pain, Palliative and Intensive Care, Dhaka Medical College Hospital, Bangladesh, between May 2020 and December 2021. A total 640 obstetric patients undergoing caesarean section (both COVID positive and suspected) were observed. The demographic and outcome data of mothers ( transferred from post-operative ward to parent ward/ICU) were collected. Informations of ultimate fate (alive/death) of operated mothers were also noted. Demographic (sex) data and outcome data of newborn baby (alive/dead) were also included. The statistical analysis was carried out by using the Statistical Package for Social Sciences version 22.0 for Windows. Results: In this study, the age of the most (n=532, 83.13%) of the pregnant mothers belongs to 18-30 years of age group, remaining 16.86% patients are within the age group of 31-45 years (n=108). Although 18.75% study subjects were illiterate below class VIII(31.25), SSC(17.97%), HSC(16.40%), Graduate(12.5%), masters(3.13%)], miscellaneous type of occupational status [home-maker(70%), service holder(19.85%), entrepreneurship(1.56%) & others(8.59%. and came from different category of social class[ most of the patients belong to lower(54.68%) and lower middle class (27.81%) socioeconomic status]. Among total study sample (n=640), 55.63% (n=356) patients were infected with COVID 19 virus confirmed by RT-PCR and 44.38% (n-284) mothers were clinically COVID infected or suspected cases. The majority of the pregnant mothers (n=565. 88.28%) experienced sub-arachnoid block or spinal anaesthesia whereas only 6.09% (n=39) patients got experience of general anaesthesia. Apparently, 93.44% (n=598) of mothers come back to the parent ward after observing in post-operative ward. Of them, (n=640), 2.19% of mothers were not survived in operation theatre or post-operative ward and 4.34% (n=21)of patients had to go to Covid dedicated Intensive Care Unit. Survivors mothers (n=619, 96.72%) were greater than that of non-survivors (n=21, 3.28%). Among the delivered new born babies, the number of female babies (n=330, 51.56%) were slightly higher than that of male (n=310, 48.44%). In a total 640 babies, 560 babies (87.50%) were survived but 12.50% (n-=80 ) of babies were not survived. Conclusions: This observational study represents that among 640 number of COVID positive or suspected pregnant mothers who were undergoing caesarean section , 93.44% of mothers come back to the parent ward, 2.19% of mothers were expired in operation theatre or post operative ward because of complications. Unfortunanely, 4.34% of mothers had experience to go to Intensive Care Unit. Survivors mothers were greater than that of non-survivors. New born babies of confirmed and suspected COVID mothers were slightly female predominant. Total of them, 87.50% of babies were survived. J Dhaka Med Coll. 2022; 31(2) : 187-193